The Influence of the Precipitation/Ageing Temperature on a Cu/ZnO/ZrO2 Catalyst for Methanol Synthesis from H2 and CO2. Issue 6 (29th April 2014) - Frei, Elias; Schaadt, Achim; Ludwig, Thilo; Hillebrecht, Harald; Krossing, Ingo
Abstract For heterogeneous catalysts, the constitution of the precursor is an important parameter to adjust the properties of the active catalyst. Therefore, we examined the influence of the temperature during the precipitation process and during the ageing time in the mother liquor for a Cu/ZnO/ZrO2 catalyst system obtained through a coprecipitation route. The variation of the temperature affects the ratio and crystallinity of the precursor phases zincian malachite and aurichalcite, as detected by powder XRD (phase and line width) and FTIR spectroscopy (characteristic asymmetric CO stretching modes of the carbonate anions at <![CDATA[$\tilde \nu $]]> <inline-graphic xlink:href="ark:/27927/pghh51x8hh" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />=1600–1100 cm−1). Therefore, the precatalyst surface area (As, BET) and pore distribution are adjustable (i.e., As, BET of 190 m2 g−1 was reached). The influence of the synthesis conditions on the catalysts activity for methanol production was analyzed and discussed up to the level of productivity/activity testing at 413/513 K and 40 bar total H2/CO2 pressure. The best catalyst showed a methanol productivity of 9.16 mmol gcat−1 h−1 (513 K, 40 bar, and gas hourly space velocity=8000) and is better than an industrial catalyst tested under the same conditions (8.34 mmol gcat−1 h−1). However, despite considerable differences in the precursor and precatalyst structure and morphology, their influence on the methanol productivity is only small. This demonstrates that the active catalyst is formed under reaction conditions.